The research of modern condition of the glacier Tuyuksu (Journal of Geography and Environmental Management, 2016)
Meteorological data on Tuyuksu glacier are the main source of analysis of climate change in glacial- nival zone of the northern slope of the Ile Alatau . This article describes the basic meteorological variables (temperature , precipitation) for the period 1972-2008 gg. on glaciological station Tuyuksu -1 and meteorological stations Mynzhilki Almaty and tendencies of their changes . In addition, the values of annual evaporation E , the average rate of change of evaporation over 10 years and moistening coefficient Ku were calculated. In accordance with the gradations of humidity on N. Ivanov viewed stations were assigned to moisture zone. The correlation dependencies between meteorological parameters and the parameters of the glacier were built.
Keywords: Tuyuksu glacier; climate change